2020
DOI: 10.1097/pr9.0000000000000849
|View full text |Cite
|
Sign up to set email alerts
|

Pain perception and processing in individuals with posttraumatic stress disorder: a systematic review with meta-analysis

Abstract: Supplemental Digital Content is Available in the Text. Posttraumatic stress disorder encompasses latent subgroups of individuals with qualitative differences in pain perception.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…Pain and trauma are highly comorbid conditions ( 1 6 ), especially among the military and veteran population ( 7 , 8 ), and both are associated with dramatic changes in the brain structure and function ( 9 , 10 ). Using experimental pain and task-based functional magnetic resonance imaging (fMRI), we and others have repeatedly shown that men and women with trauma demonstrate dysregulated behavioral ( 11 , 12 ) and brain response to pain, depicted in the increased pain avoidance and dysregulated modulatory response within interoceptive, reward, and frontal modulatory networks ( 13 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Pain and trauma are highly comorbid conditions ( 1 6 ), especially among the military and veteran population ( 7 , 8 ), and both are associated with dramatic changes in the brain structure and function ( 9 , 10 ). Using experimental pain and task-based functional magnetic resonance imaging (fMRI), we and others have repeatedly shown that men and women with trauma demonstrate dysregulated behavioral ( 11 , 12 ) and brain response to pain, depicted in the increased pain avoidance and dysregulated modulatory response within interoceptive, reward, and frontal modulatory networks ( 13 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis of pain processing and perception in healthy adults revealed no significant differences in pain intensity ratings or pain tolerance in individuals with vs without PTSS. 43 However, when they stratified their sample by individuals with combat-related trauma and accident-related trauma, they found significantly increased and decreased thresholds for pain, respectively. 43 Therefore, youth with higher PTSS and chronic pain appear to be more similar to adults that have experienced combat-related trauma in their responses to the CPT.…”
Section: Discussionmentioning
confidence: 97%
“… 43 However, when they stratified their sample by individuals with combat-related trauma and accident-related trauma, they found significantly increased and decreased thresholds for pain, respectively. 43 Therefore, youth with higher PTSS and chronic pain appear to be more similar to adults that have experienced combat-related trauma in their responses to the CPT. The frontal cerebral cortex is the area of the brain that governs rational thought.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Independent research into the opioid dysregulation schema of patients suffering from both conditions reveal portentous underpinnings of decreased pain thresholds and reduced endogenous opioid levels 4 . When compared to age‐matched cohorts without PTSD, those with the disorder retain significantly higher risks of developing subsequent dependence after initial exposure to opioid analgesia 5,6 . The higher risk of opioid use disorder for these patients is due to the shared vulnerability model, the mutual maintenance model whereby trauma and stress worsen pain and vice versa, and the fact that opioids may not only relieve physical pain but also relieve some of the disabling PTSD symptoms through effects on the hypothalamic‐pituitary‐adrenal (HPA) axis 3 .…”
Section: Introductionmentioning
confidence: 99%